A new mean value of failure criteria updated compensation method based on heuristic MAP estimation for tensile damage diagnosis of high-strength aluminum alloy. (June 2022) - Ai, Yibo; Ma, Ning; Zhang, Tao; Zhang, Weidong
Highlights: A new algorithm based on the heuristic MAP estimation algorithm is proposed for solving the mean deviation problem caused by material dispersion. A research framework for performance degradation-based fault diagnosis and life prediction is proposed. Two failure modes of tensile damage and fatigue damage were done. Abstract: The deviations between characteristic parameters of some individual samples and statistical expectations are relatively large because of the material dispersion. To solve this problem, a mean value updating and compensation algorithm for failure criteria based on heuristic maximum a posteriori estimation has been proposed, the failure criterion would be updated with new samples, the difference between new and old failure criteria would be used to compensate for the new sample to improve the accuracy of the fault diagnosis of the material damage to the gearbox shell. In this study, a failure mode of tensile damage has been done and the effectiveness of this method has been demonstrated.